Prove the following using the principle of mathematical induction for all n ∈ N
n (n + 1) (n + 5) is a multiple of 3.
Let the given statement be P(n), as
P(n):n(n + 1)(n + 5) is a multiple of 3.
First, we check if it is true for n = 1,
P(1):1(2)(6) = 12 is a multiple of 3;
∴ It is true for n = 1.
Now we assume that it is true for some positive integer k, such that
P(k):k(k + 1)(k + 5) = 3m where m ∈ N
We shall prove that P(k + 1)is true,
P(k + 1):(k + 1)(k + 2)(k + 5 + 1)
⇒ (k + 1)(k + 2)(k + 5) + (k + 1)(k + 2)
⇒ k(k + 1)(k + 5) + (2)(k + 1)(k + 5) + (k + 1)(k + 2)
⇒ 3m + (k + 1)[2k + 10 + k + 2]
⇒ 3m + (k + 2)(3k + 12)
⇒ 3m + 3(k + 2)(k + 4)
⇒ 3[m + (k + 2)(k + 4)]
We proved that P(k + 1) is true.
Hence by principle of mathematical induction it is true for all n ∈ N.